2010
DOI: 10.1111/j.1471-4159.2009.06563.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential sensitivity of the inner ear sensory cell populations to forced cell cycle re‐entry and p53 induction

Abstract: Previous studies have shown that the maintenance of postmitotic state is critical for the life-long survival of the inner ear mechanosensory cells, the hair cells. A general concept is that differentiated, post-mitotic cells rapidly die following cell cycle re-entry. Here we have compared the response of postnatal cochlear (auditory) and utricular (balance) hair cells to forced cell cycle reactivation and p53 up-regulation. Forced S-phase entry was triggered through the human papillomavirus-16 E7 oncogene mise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 48 publications
(53 reference statements)
4
21
0
Order By: Relevance
“…Specifically, the numerous doublets of EdU-labeled Deiters' cells and the signs of impaired separation of the nuclei of the doublets suggested that the cell cycles were incomplete. Interestingly, this has also been found in developing hair cells after cell cycle reactivation [11, 41]. We found that p53, a mediator of cycle arrest and apoptosis, was upregulated in Deiters' cells of AdcD1-infected cochkeas, in most cases in the cell doublets.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Specifically, the numerous doublets of EdU-labeled Deiters' cells and the signs of impaired separation of the nuclei of the doublets suggested that the cell cycles were incomplete. Interestingly, this has also been found in developing hair cells after cell cycle reactivation [11, 41]. We found that p53, a mediator of cycle arrest and apoptosis, was upregulated in Deiters' cells of AdcD1-infected cochkeas, in most cases in the cell doublets.…”
Section: Discussionsupporting
confidence: 68%
“…Upon forced proliferation, γH2AX induction has been shown in neurons of the central nervous system and in the inner ear hair cells, and was found to lead to apoptosis of these highly differentiated cells [10, 11]. Upon DNA damage triggered by genotoxic agents, activation of other components of the DDR pathway, besides H2AX, has been shown in postmitotic neurons and epithelial cells [12-14], but, surprisingly, not in astrocytes, even though these cells were found to be DNA repair-proficient [9].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, we did observe a small number of hair cells that were transduced with Ad.GFP, and we have not yet ruled out that the BrdU-positive/myosin VIIA-positive cells were pre-existing hair cells that reentered the cell cycle after being transduced with Ad.MT58A. Conditional deletion of the retinoblastoma protein or ectopic expression of the HPV-16 E7 oncogene within hair cells can drive their reentry into the cell cycle, so it is reasonable to suspect that ectopic expression of c-Myc may produce similar effects [55][57], [59], [62], [83]. If the BrdU-positive/myosin VIIA-positive cells we observed did originate from the supporting cell population infected with Ad.MT58A, then ectopic c-Myc expression may be capable of dedifferentiating supporting cells into cells with characteristics of otic progenitors.…”
Section: Discussionmentioning
confidence: 97%
“…Directly reprogramming postmitotic supporting cells into hair cells could decrease the size of the supporting cell population without some form of nonautonomous cell replacement [92], which makes restoration of self-renewal capacity vital to the reprogramming strategy. Cyclins, cyclin dependent kinase inhibitors (CDKIs), and pocket proteins have been shown to regulate proliferation and cell cycle exit during development of the sensory epithelium, and a growing list of these genes have been targeted to force reentry of supporting cells into the cell cycle [41], [54][62], [83], [94][98]. MYC controls the expression and activity of various cyclins, CDKIs, and pocket proteins [65], [76], which may make it more suitable for orchestrating the complex fluctuations of cell cycle proteins that are necessary to drive efficient progression through the various restriction points.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo approaches force inner ear supporting cells to re-enter the cell cycle followed by directed terminal differentiation into hair cells and supporting cells using viral vectors, including adeno-associated virus serotype 2 or adenovirus serotype 5 [33,144,145,146,147,148]. In vitro approaches use stem cell populations and culture them into hair cell-like cells and seed hair cell-like cells onto the cochlea [47,149].…”
Section: Translational Significance and Future Directionsmentioning
confidence: 99%